Practicing “The Ideal Islamic Doctrines” Among Muhammadiyah Members in Karangtengah Imogiri - Parjiman, Parjiman (IJISH (International Journal of Islamic Studies and Humanities), 2018)
Muhammadiyah was established as the masterpiece of "The Enlightenment". This organization is emerged a Negari Ngayogyakarto Hadiningrat where becomes the center of Javanese’s culture and civilization. Yogyakarta is a land of civilization untouched by the Dutch colonial and even recognized sovereignty as a sovereign state. However, the people still believed supersititous (takhayul and khurafat) and still performed bid’ah at that time and these attitude became their identity. Therefore, the biggest deram of the Kyai Dahlan, the founder of Muhamamdiyah is to create the ideal Islamic society with the purest Islamic teaching. The ideal society is where the Islamic values is implemented and colloring the entire aspects of life. Thus, the people is characterizes as a religious and obedient, loyal, civilized, welfare, deliberate, courteous, progressive, leading, and discipline. This society represents a moderate society that can create a balanced culture and civilization. In this research, I present branch of Muhammadiyah of Karangtengah as a sample. The results showed that religious adherence of Karangtengah people was relatively good. In political engagement, they are not actively involved, because the members of Muhammadiyah are expected to not involved in political practice. Additionally, mosque as the place for praying is well provided and it is affecting the existence of Muhammadiyah among Muslims and the village government.